Polyphenolic Composition and Antioxidant Activity of Uncaria tomentosa Commercial Bark Products - Mirtha Navarro; Elizabeth Arnaez; Ileana Moreira; Alonso Hurtado; Daniela Monge; Maria Monagas (MDPI AG, 2019)
Uncaria tomentosa, which is widely commercialized as an herbal medicine, constitutes an important source of secondary metabolites with diverse biological activities. For instance, we have previously reported, for the first time, of a polyphenolic profile rich in proanthocyanidins from extracts of U. tomentosa plants, as well as their antioxidant capacity, antimicrobial activity on aerial bacteria, and cytotoxicity on cancer cell lines. These promising results prompted this research to evaluate the polyphenolic contents of U. tomentosa commercial products. We report a detailed study on the polyphenolic composition of extracts from U. tomentosa bark products (n = 18) commercialized in Costa Rica and Spain. Using HPLC-DAD/TQ-ESI-MS, a total of 25 polyphenolic compounds were identified, including hydroxybenzoic and hydroxycinnamic acids, flavan-3-ol monomers, procyanidin dimers, procyanidin trimers, as well as propelargonidin dimers. Our findings on the polyphenolic profile for all commercial samples show analogous composition to previous reports on U. tomentosa bark material, for instance a 41−49% content of procyanidin dimers and the presence of propelargonidin dimers (8−15%). However, most of the 18 commercial samples exhibit low proanthocyanidin contents (254.8−602.8 µg/g), more similar to previous U. tomentosa inner bark reports, while some exhibit better results, with one sample (SP-2) showing the highest contents (2386.5 µg/g) representing twice the average value of all 18 commercial products. This sample also exhibits the highest total phenolics (TP) and total proanthocyanidins (PRO) contents, as well as the highest Oxygen Radical Absorbance Capacity (ORAC) value (1.31 µg TE/g). One-way Analysis of Variance (ANOVA) with a Tukey post hoc test indicated significant difference (p < 0.05) between products from Costa Rica and Spain for TP and PRO findings, with samples from Spain exhibiting a higher average value. In addition, Pearson correlation analysis results showed a positive correlation (p < 0.05) between TP, PRO, and ORAC results, and an especially important correlation between ORAC antioxidant values and procyanidin dimers (r = 0.843, p < 0.05), procyanidin trimers (r = 0.847, p < 0.05), and propelargonidin dimers (r = 0.851, p < 0.05) contents. Finally, Principal Component Analysis (PCA) results indicated some variability in the composition regardless of their origin. However, only one sample (SP-2) stands out significatively, showing the highest PC1 because of its particularly high proanthocyanidins contents, which could be attributed to the 15% bark polyphenolic extract labeled in this commercial product, which differentiate this sample from all other 17 commercial samples. Therefore, our findings confirmed previous results on the value of extracts in the elaboration of potential commercial products from U. tomentosa, rich in proanthocyanidins and exhibiting high antioxidant activity.